A Matched Comparison of the Benefits of Breast Reduction on Health-Related Quality of Life. Issue 4 (October 2021) - Elfanagely, Omar; Othman, Sammy; Rios-Diaz, Arturo J.; Cunning, Jessica R.; Whitely, Cutler; Butler, Paris; Fischer, John P.
Abstract : Background: Breast reduction surgery has consistently fallen within the top 10 surgical procedures performed by plastic surgeons. This is because of its capability to relieve the physical and psychological impact of macromastia. Although numerous women pursue consultation, many never undergo the procedure. The authors aim to quantify the impact of breast reduction surgery on quality of life by comparing patients who underwent breast reduction surgery with those who did not. Methods: Patients seeking breast reduction surgery between 2016 and 2019 were identified. As standard-of-care, patients are surveyed during the consultation visit and postoperative visits using the BREAST-Q. The preoperative survey was readministered a second time for those who did not undergo breast reduction surgery. Propensity score matching, based on patient demographics, comorbidities, and breast examination, was used to balance baseline characteristics. Results: A total of 100 propensity-matched patients were identified (operative, n = 78; nonoperative, n = 22). Mean participant age was 39.5 ± 25 years and mean body mass index was 31.1 ± 7.4 kg/m 2 . Quality of life significantly improved in each domain for those in the operative group ( p < 0.05). Those who did not undergo breast reduction surgery realized no improvement in quality of life and had a downward trend in quality of life across two of the four domains. Conclusions: Breast reduction surgery offers a significant improvement in quality of life for macromastia. This matched study demonstrates that patients who are able to undergo breast reduction surgery have a statistically significant improvement in all aspects of quality of life, whereas nonsurgical patients experience no benefit with time, with a trend toward deterioration in specific domains.